Impact of salinity on the morpho-biochemical traits of hydroponically cultivated Spinacia oleracea L. - Archana Naik; Shekhar Tidke; Mahadev Chambhare; Ravindra Bansode; Panchshila S. Kabnoorkar (BioTechnologia)
Background Spinacia oleracea, a nutrient-dense vegetable composed of 91% water, 4% starch, and 3% protein, is a staple in the Indian diet. However, salinity stress can hinder its growth. This study examines the effects of salinity on the morpho-biochemical traits of spinach in a hydroponic system.